1983
DOI: 10.1136/pgmj.59.698.791
|View full text |Cite
|
Sign up to set email alerts
|

Erythema nodosum progressing to pyoderma gangrenosum as a complication of Crohn’s disease

Abstract: Summary Erythema nodosum occurs more frequently than pyoderma gangrenosum in Crohn’s disease. We report the occurrence of both lesions in a woman with Crohn’s disease and the transformation of one to the other. Pyoderma gangrenosum has been described at the site of previous trauma in Crohn’s disease and at the site of other skin conditions in other circumstances, but, to the best of our knowledge, actual progression from erythema nodosum to pyoderma gangrenosum has been reported on only one prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Nevertheless, even if it is usually managed successfully with combined topical therapy and general treatment of the underlying IBD, in some cases it may have a more severe course [32]. Pyoderma gangrenosum was previously reported as progressing from erythema nodosum lesions [33], which could partially account for the increased frequency of erythema nodosum compared to pyoderma gangrenosum. Ophthalmological manifestations are another type of wellrecognized immune-related extraintestinal manifestations of IBD, with a reported prevalence of up to 13%, more common in CD than in UC patients [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even if it is usually managed successfully with combined topical therapy and general treatment of the underlying IBD, in some cases it may have a more severe course [32]. Pyoderma gangrenosum was previously reported as progressing from erythema nodosum lesions [33], which could partially account for the increased frequency of erythema nodosum compared to pyoderma gangrenosum. Ophthalmological manifestations are another type of wellrecognized immune-related extraintestinal manifestations of IBD, with a reported prevalence of up to 13%, more common in CD than in UC patients [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of pyoderma gangrenosum evolving from preceding erythema nodosum also have been reported. 79 The diagnosis is made clinically, although wound swabs and a skin biopsy may be needed to exclude other conditions. There are no pathognomonic histological features, generally revealing only diffuse neutrophil infiltration and dermolysis.…”
Section: Eim Of the Skinmentioning
confidence: 99%
“…For pediatric patients, Dotson et al (12) also reported that pyoderma gangrenosum was more common in CD than UC among a total of 1,009 patients with a total prevalence of 0.3% (3 of 1,009). Pyoderma gangrenosum is known to be related with colonic involvement, EN, and arthritis (2,50,51). The correlation with the underlying disease activity of pyoderma gangrenosum is not clear to date; however, it usually resolves with treatment of the underlying IBD (2,15,51).…”
Section: Pyoderma Gangrenosummentioning
confidence: 99%